Evaluation of a school-based, teacher-delivered psychological intervention group program for trauma-affected Syrian refugee children in Istanbul, Turkey - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2017)
Objective: The purpose of this study was to evaluate an innovative, protocol-based, group cognitive behavioral therapy (CBT) program delivered by trained teachers to reduce emotional distress and improve psychological functioning among the war-traumatized Syrian refugee students living in Istanbul. Methods: A total of 32 participants, aged between 10 and 15 years (mean = 12.41, SD = 1.68) and mostly females (m/f = 12/20) were randomly selected from a sample of 113 refugee students based on their trauma-related psychopathology as reflected in the Child Post-Traumatic Stress -Reaction Index (CPTS-RI) total score. The treatment program was implemented by the teachers trained by the study team to deliver a weekly, eight-session, protocol-based intervention in school setting. The degree of the fidelity to the original program was tested via video-recordings and subsequent analyses of the sessions. Effectiveness of the intervention was evaluated by a pre-test/post-test comparison using the CPTS-RI, Spence Children's Anxiety Scale (SCAS), and Strengths and Difficulties Questionnaire (SDQ). Results: All participants were accompanied minors. A significant proportion of them had either witnessed or been personally exposed to traumatic events. Statistically significant reduction in post-intervention evaluation was observed in the SCAS total score (t = 3.73, p = 0.001); CPTS-RI total score (t = 2.72, p = 0.011) and in the intrusive (t = 3.88, p = 0.001) and arousal (t = 2.60, p = 0.015) symptoms of the post-traumatic stress disorder (PTSD). In line with improvement in emotional problems as revealed in the anxiety and PTSD scales, the SDQ subcategory of the emotional problems was the only symptom area that showed a significant improvement (t = 2.85, p = 0.008). No significant change was seen in the SDQ subcategories of conduct (t = 1.01, p = 0.32), hyperactivity (t = 1.30, p = 0.20), peer problems (t =.66, p = 0.51), or in prosocial behavior (t = 2.15, p = 0.039). A significant proportion of the participants did no longer meet the diagnostic threshold for anxiety (p = 0.001) and PTSD (p = 0.021) after completion of the intervention. However, the post-intervention SDQ subcategories and the total SDQ score showed no significant difference as compared with the pre-intervention group. Conclusions: To the best of our knowledge, this is the first interventional study reporting promising results from a school-based, teacher-led and culturally sensitive psychological intervention program for refugee children in Turkey. Such protocol-based interventions need to be examined in controlled designs and larger samples so that a well-established intervention can be created and disseminated to provide the psychosocial support for this vulnerable and traumatized population.
Keywords: Post-traumatic stress disorder; cognitive behavioral therapy; refugee; children; school-based; POSTTRAUMATIC-STRESS-DISORDER; MENTAL-HEALTH PROBLEMS; DIFFICULTIES QUESTIONNAIRE; IMMIGRANT CHILDREN; WAR; SYMPTOMS; ANXIETY; ADOLESCENTS; PSYCHOPATHOLOGY; METAANALYSIS